Load-Dependent Copper Loss Analysis in Educational-Scale Transformers: An Experimental Approach - Pratama, Defrianto (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2025)
This study aims to experimentally investigate the effect of load resistance variation on copper loss and transformer efficiency at the laboratory scale. Two transformer configurations—step-up and step-down—were tested with load resistances ranging from 10 to 500 Ohms. Measurements of voltage, current, and power were taken on both the primary and secondary sides to calculate copper loss and efficiency. The experimental results demonstrate a nonlinear inverse relationship between load resistance and copper loss, consistent with theoretical predictions. The step-up configuration exhibited higher copper loss under low-load conditions, whereas the step-down transformer showed a more stable efficiency profile across varying loads. Statistical validation, as indicated by the coefficient of determination (R² > 0.98) and Root Mean Square Error (RMSE < 0.08 W), demonstrates a strong agreement between the theoretical models and experimental data, confirming the model's accuracy and the reliability of the experimental setup. These findings have practical implications for optimizing transformer loading strategies to reduce long-term energy losses and improve operational efficiency. Moreover, the results support the development of vocational education laboratory modules that link Theory with hands-on learning, enhancing students' understanding of real-world transformer performance and energy efficiency concepts. This study contributes to the field by validating a theoretical model with experimental data, highlighting critical load-loss relationships in transformer operation, and providing a practical framework for both industry applications and technical education.